Energy in the European community - Commission of the European Communities (Luxembourg : Office for Official Publications of the European Communities, 1991)
The book examines the issues of Energy in European Community with particular reference with the Community position in the world energy market.
"Deadline 92"--Cover.
"Catalogue number: CB-826-1737-8"--T.p. verso.
Includes bibliographical references (p. 43-45).
asm; 14/01/2019
Loans
Keywords: Energy policy